Psychoeducation Outreach to Families Through The Live Instagram Of The Family Learning Center (PUSPAGA) Surabaya City - Betty Wulan Safitri; Siti Jaro'ah (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
The family, as the primary source of a child's education, plays a crucial role in the child's growth and development. Particularly for adolescents who face mental health challenges as they transition from childhood to adulthood. To address these issues, psychoeducation for both parents and children is essential. This study examines the effectiveness of the PUSPAGA psychoeducation outreach program via Instagram Live in Surabaya. Utilizing qualitative research methods, data were collected through interviews to understand the program's impact. The findings indicate that the program successfully raises awareness about mental health and family well-being, leveraging the broad reach of social media. Despite challenges such as technical limitations and varying audience engagement, the program has been positively received, highlighting the potential of digital platforms in delivering psychoeducational content. Recommendations for future program development are provided to enhance the effectiveness and reach of similar initiatives.